Determination and Optimization of Feeding Device Parametres in the Plant for Preparing Liquid Feed Mixtures - Solonshchikov Pavel (Sciendo, 2021)
Feeding young animals is a very important stage during their growing-up period, but in order to provide them with essential nutrients, they are fed with liquid feeds, whole milk substitute in particular (WMS). The technique for reconstituting WMS consists of dissolving it in water followed by mixing, but it is significant to follow the cooking recipe strictly, so it is necessary to develop a system with a feeding (dosing) device that will make it possible to solve this problem. Theoretical and experimental studies of the feeding device have been conducted in order to optimize the technological process of mixing liquid feed. Theoretically, the quality of determining the mixture during dosing was established for the purpose of further research. The influence of the design and technological parameters of the feeding device was experimentally studied, and its efficiency was evaluated. It was found that as the inclination angle α increases from 67,50 to 700, the rotation speed n being from 850 to 1500 min−1, the maximum probability of staying in the tolerance field ΔP=96% is reached, and feed discharge Q ranges from 540 to 660 kg h−1. The research makes it possible to develop a feeding device at the design stage, meeting the requirements of the recipe, having high discharge rates and the lowest energy consumption.